2017
DOI: 10.3389/fphar.2017.00156
|View full text |Cite
|
Sign up to set email alerts
|

HuangQin Decoction Attenuates CPT-11-Induced Gastrointestinal Toxicity by Regulating Bile Acids Metabolism Homeostasis

Abstract: Irinotecan (CPT-11) is a potent chemotherapeutic agent, however, its clinical usage is often limited by the induction of severe gastrointestinal (GI) toxicity, especially late-onset diarrhea. HuangQin Decoction (HQD), commonly used for the treatment of GI ailments, has been proved could significantly ameliorate the intestinal toxicity of CPT-11. To reveal the mechanisms of CPT-11-induced toxicity and the modulation effects of HQD, a previous untargeted metabolomics study was performed and the results indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Metabolomics has been used as important technique for interpreting pharmacological mechanisms of TCM formulae under the guidance of systematic theory (Li et al, 2011 ; Li and Zhang, 2013 ). Indeed, there have been an increasing number of TCM studies applying metaboliomics (Lu et al, 2014 ; Cao et al, 2015 ; Wang et al, 2015 , 2017 ). Wen-Luo-Tong (WLT) is an herbal formula ointment for topical application.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics has been used as important technique for interpreting pharmacological mechanisms of TCM formulae under the guidance of systematic theory (Li et al, 2011 ; Li and Zhang, 2013 ). Indeed, there have been an increasing number of TCM studies applying metaboliomics (Lu et al, 2014 ; Cao et al, 2015 ; Wang et al, 2015 , 2017 ). Wen-Luo-Tong (WLT) is an herbal formula ointment for topical application.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, alteration of hCE2 activity may lead to the fluctuation of intestinal SN‐38 concentration, which would determine the risk of intestinal toxicity (X. W. Wang, Zhu, & Markowitz, ; Xiao et al, ). Although a large number of clinical drugs, such as loperamide vhydrochloride, cholestyramine, and levofloxacin, have been regarded as the promising options for the prevention of delayed diarrhea caused by CPT‐11, the improper mechanism and dosage are common causes for treatment failure (X. Wang et al, ). Moreover, herbal medicine PHY906 has been reported to attenuate the intestinal toxicity induced by CPT‐11 (Cui et al, ; Lam et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a large number of clinical drugs, such as loperamide vhydrochloride, cholestyramine, and levofloxacin, have been regarded as the promising options for the prevention of delayed diarrhea caused by CPT-11, the improper mechanism and dosage are common causes for treatment failure (X. Wang et al, 2017). Moreover, herbal medicine PHY906 has been reported to attenuate the intestinal toxicity induced by CPT-11 (Cui et al, 2017;Lam et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…LC-IT-TOF/MS was used to clarify which active compounds are actually existing in water decoction of HQD. One milliliter of standard decoction HQD ( Wang X. et al, 2017 ) was dissolved in a suitable amount of 80% (v/v) methanol with the assistant dissolve effect of DMSO by ultra-sonication and subsequently centrifuged (16000 rpm, 4°C) for 10 min. The supernatants were filtered and analyzed on a ZORBAX SB-C18 rapid resolution HT (2.1 mm × 100 mm, 1.8 μm) (Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…HuangQin decoction (HQD) is a basic formula listed in Treatise on Exogenous Febrile Disease written by Zhongjing Zhang. It has been widely used in China for more than 1800 years on the treatment of gastrointestinal (GI) ailments, including diarrhea, abdominal spasms, vomiting, and nausea ( Wang X. et al, 2017 ). Recent studies have revealed that PHY906, a modified formulation derived from HQD, could ameliorate chemotherapy-induced GI toxicity and enhance the therapeutic efficacy of irinotecan, capecitabine and other antitumor drugs ( Lam et al, 2010 ; Saif et al, 2010 ; Wang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%